The support of the Kingdom of Saudi Arabia to West African countries during the reign of King Fahd – may God have mercy on him – through educational facilities - Al- Hudhali, Sarah Massad Hamdan (Journal of Humanities & Social Sciences, 2020)
The Kingdom of Saudi Arabia has achieved many accomplishments in various fields and was distinguished by the service of Islam and Muslims. and the pursuit of Islamic unity, its cultural efforts towards Muslims in general, and West Africa in particular is one of the pillars of this Islamic unity, and this research was tested to highlight these efforts presented to Muslims in West Africa. I choose this research to display these efforts. Research contains three fields: mosques and quranic cells, schools, and institutions,. college and Universities, I follow history research which based on observation and induction.